2020
DOI: 10.1371/journal.pone.0231202
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiac remodeling secondary to chronic volume overload is attenuated by a novel MMP9/2 blocking antibody

Abstract: ObjectiveMonoclonal antibody derivatives are promising drugs for the treatment of various diseases due to their high matrix metalloproteinases (MMP) active site specificity. We studied the effects of a novel antibody, SDS3, which specifically recognizes the mature active site of MMP9/2 during ventricular remodeling progression in a mouse model of chronic volume overload (VO). MethodsVO was induced by creating an aortocaval fistula (ACF) in 10-to 12-week-old C57BL male mice. The VO-induced mice were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…No difference between sexes was observed in any cardiac phenotype. These results confirmed that the LV VO was successfully established in ACF mice, consistent with previous publications ( 24 , 25 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…No difference between sexes was observed in any cardiac phenotype. These results confirmed that the LV VO was successfully established in ACF mice, consistent with previous publications ( 24 , 25 ).…”
Section: Resultssupporting
confidence: 93%
“…In adult animals, ACF not only induces RV VO but also produces LV VO ( 24 , 25 ). In past studies, we demonstrated that ACF induces RV VO at neonatal and prepubertal animals ( 13 , 18 , 20 , 26 ), and VO induces different responses among neonatal, prepubertal, and adult RVs ( 13 , 26 , 27 ), highlighting the importance of developmental stage-specific analysis of the effect of VO on RV remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of myocardial ECM via MMPs including MMP-2 and MMP-9 is a key trigger of adverse ventricular remodeling 20 23 , which is an important pathogenesis of DCM. To elucidate the molecular mechanisms underlying the development of DCM after myocarditis, we evaluated the expression and activation of MMP-2 and MMP-9 in the bulk heart tissues on day 56.…”
Section: Resultsmentioning
confidence: 99%
“…Ruzicka et al reported an initial (within one week of induced volume overload) increase in elastin concentration but then a decrease of elastin concentration below control levels 10 weeks after induced volume overload [114]. The reduction of ECM turnover in volume overloaded LV was related to a phenotype change of fibroblasts into hypofibrotic type [116] and increased MMP expressions from macrophages or mast cells [117][118][119]. An increased collagen III/I ratio was also noted in the compensated stage of the remodeling [114].…”
Section: Biomechanical Adaptations In Volume Overload Myocardiummentioning
confidence: 99%